Case Report: Phenotypic and genetic characterization of a presumptive sporadic hypothalamic hamartoma in a standard Schnauzer dog - Liatis, Theofanis; Attree, Elizabeth; Ruiz De Alejos Blanco, Laura; Santens, Patrick; De Stefani, Alberta; Psifidi, Androniki (Frontiers in Veterinary Science, 2025)
IntroductionHypothalamic hamartoma (HH) is a rare suprasellar developmental lesion that resembles ectopically located grey matter within the hypothalamus. Genetic mutations in genes involved in the sonic hedgehog intracellular pathway have been reported in humans with HH. Hypothalamic hamartoma has been reported in dogs; however, no genetic mutation has been associated with it. The aim of this study was to phenotypically and genetically characterize presumptive sporadic HH in a dog.Case presentationA 7-month-old male Schnauzer was presented with chronic left head tilt, episodes of imbalance, circling to the left, and continuous repetitive movements of the head and neck to the left. These episodes could increase with stress or interaction, and the dog could not be distracted out of it. Clinical examination was normal. Neurological examination revealed a continuous repetitive involuntary movement of the head and neck to the left and left ocular torsion. Haematology and serum biochemistry were within normal limits. Magnetic resonance imaging of the head raised a suspicion of HH. Whole genome sequencing and genetic analysis identified germline variants with a high predicted impact on the encoding proteins in the candidate genes SEPTIN8, UBXN10, and BLOC1S1, which are involved in ciliogenesis and may be associated with the manifestation of HH in this dog.ConclusionSporadic HH should be considered in the differential diagnoses list for a young dog with chronic progressive intracranial neurologic signs and may be genetically associated with germline mutations in primary cilia-related genes.